Hubungan Pendidikan, Pengetahuan Dan Dukungan Suami Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Tabunganen Kabupaten Barito Kuala Tahun 2016 - Norfai Norfai; Khairul Anam; Deni Suryanto (HB PRESS, 2016)
Anemia is a condition in which the hemoglobin level in the blood is reduced or lower than normal which is less than 11.0 gr/dl. Cases of iron deficiency anaemia in pregnant women in Barito Kuala District Tabunganen Public Health Center Work Area by 71.2% with the number 2 ranked highest of the 19 health centers located in Barito Kuala. This research aims to study and explain the relationship of education, knowledge and support her husband with the incidence anaemia in pregnant women in Barito Kuala District Tabunganen Public Health Center Work Area. This research is an analytic survey with cross sectional approach. The sample of the as many as 81 respondents with the sample collection in purposive sampling. Data were collected using a questionnaire, the results of data collection were analyzed using univariate statistics, bivariate with chi square test using a computer program tools. So the results obtained that respondents who suffer from anaemia of 65.4%. Variables significantly associated with the incidence anaemia (p-value < 0.05) is education, knowledge, and support her husband. Suggestion given is increasing knowledge by way of counseling to the pregnant women and the husband on the importance of maintain the health of mothers during pregnancy by means of inspections pregnancy with regular, especially examination of levels of hemoglobin. Keywords: Education, Knowledge, Support Husband, The Incidence Anaemia in Pregnant Women